Differential Adaptation of Propionibacterium freudenreichii CIRM-BIA129 to Cow’s Milk Versus Soymilk Environments Modulates Its Stress Tolerance and Proteome - Tarnaud, Florian; Gaucher, Floriane; do Carmo, Fillipe Luiz Rosa; Illikoud, Nassima; Jardin, Julien; Briard-Bion, Valérie; Guyomarc’h, Fanny; Gagnaire, Valérie; Jan, Gwénaël (Frontiers in Microbiology, 2020)
Propionibacterium freudenreichii is a beneficial bacterium that modulates the gut microbiota, motility and inflammation. It is traditionally consumed within various fermented dairy products. Changes to consumer habits in the context of food transition are, however, driving the demand for non-dairy fermented foods, resulting in a considerable development of plant-based fermented products that require greater scientific knowledge. Fermented soymilks, in particular, offer an alternative source of live probiotics. While the adaptation of lactic acid bacteria (LAB) to such vegetable substrates is well documented, little is known about that of propionibacteria. We therefore investigated the adaptation of Propionibacterium freudenreichii to soymilk by comparison to cow’s milk. P. freudenreichii grew in cow’s milk but not in soymilk, but it did grow in soymilk when co-cultured with the lactic acid bacterium Lactobacillus plantarum. When grown in soymilk ultrafiltrate (SUF, the aqueous phase of soymilk), P. freudenreichii cells appeared thinner and rectangular-shaped, while they were thicker and more rounded in cow’s milk utltrafiltrate (MUF, the aqueous phase of cow milk). The amount of extractable surface proteins (SlpA, SlpB, SlpD, SlpE) was furthermore reduced in SUF, when compared to MUF. This included the SlpB protein, previously shown to modulate adhesion and immunomodulation in P. freudenreichii. Tolerance toward an acid and toward a bile salts challenge were enhanced in SUF. By contrast, tolerance toward an oxidative and a thermal challenge were enhanced in MUF. A whole-cell proteomic approach further identified differential expression of 35 proteins involved in amino acid transport and metabolism (including amino acid dehydrogenase, amino acid transporter), 32 proteins involved in carbohydrate transport and metabolism (including glycosyltransferase, PTS), indicating metabolic adaptation to the substrate. The culture medium also modulated the amount of stress proteins involved in stress remediation: GroEL, OpuCA, CysK, DnaJ, GrpE, in line with the modulation of stress tolerance. Changing the fermented substrate may thus significantly affect the fermentative and probiotic properties of dairy propionibacteria. This needs to be considered when developing new fermented functional foods.